Pengembangan Media Interaktif Canva Berbasis PBL untuk Meningkatkan Kemampuan Literasi Numerasi Matematis Siswa SMP: Development of PBL-Based Interactive Canva Media to Enhance Mathematical Numeracy Literacy Skills of Junior High School Students - Popy Sigalingging; Dian Armanto; Edy Surya (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Mathematical numeracy literacy is an essential competency for students; however, assessment results and preliminary research indicate that the numeracy literacy skills of students at SMP Negeri 2 Kualuh Selatan remain very low. This issue necessitates instructional innovation through the use of digital media and interactive learning models to facilitate meaningful conceptual understanding. This study employs the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The research was conducted at SMP Negeri 2 Kualuh Selatan with 30 eighth-grade students as subjects. Data collection techniques included interviews, questionnaires, tests, and observations. Data analysis was performed using both descriptive qualitative and quantitative methods. The results of this development research indicate that: validity tests placed the media in the "highly feasible" category, with ratings of 92% from media experts, 99% from subject matter experts, and 93% from language experts; practicality tests placed the media in the "highly practical" category, with ratings of 93% from teachers and 94% from students; and effectiveness tests demonstrated that the media was effective in improving students' mathematical numeracy literacy skills, evidenced by an increase in the average score from 33.33 on the pretest to 78.33 on the posttest, with an N-Gain score of 0.68 (67.81%), falling within the medium-to-high category. Consequently, the Problem-Based Learning-based interactive Canva media developed in this study is deemed valid, practical, and effective, making it suitable as an alternative learning medium to enhance students' mathematical numeracy literacy skills.